Character Formation through Culturally Responsive Teaching: Evidence from Indonesian Primary Schools - Zulela MS (International Journal of Education and Learning Studies, 2025)
This study examines the effectiveness of Culturally Responsive Teaching (CRT) in enhancing character development among Indonesian primary students. Using a pre-test–post-test control group design, 64 fifth-grade students in a multicultural school were assigned to experimental and control groups. The experimental group received CRT-based instruction for eight weeks, while the control group followed conventional teaching. Character values measured include respect, responsibility, empathy, and tolerance. Statistical results indicated significant improvements in all domains within the experimental group (p < 0.001), with large effect sizes (Cohen’s d > 1.3). These findings demonstrate CRT’s potential to strengthen character education through culturally relevant and context-driven learning.